WOMEN'S REPRESENTATION IN LOCAL POLITICS IN BOJONEGORO: CHALLENGES AND STRENGTHENING STRATEGIES THROUGH THE 30% QUOTA POLICY - Natasya Tafary; Septi Wulandari; Ida Swasanti (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
The problem addressed in this study is the stagnation of women’s representation in the Bojonegoro District House of Representatives (DPRD), which remains at approximately 10–15% and has not reached the mandated 30% quota. This study aims to analyze the obstacles and formulate strengthening strategies for women’s political representation in local politics through the implementation of the 30% quota policy. This research is grounded in theories of gender representation, descriptive representation, and affirmative action policies in politics. The study employs a descriptive qualitative research method, with data collected through observation, in-depth interviews, and document analysis. The findings reveal that the implementation of the 30% quota policy in legislative elections tends to be merely administrative and has not substantially increased women’s electoral success. The main obstacles include entrenched patriarchal culture, limited political party support, and electoral constraints such as insufficient campaign funding and weak political networks. Based on these findings, the study recommends strengthening political party commitment to cadre development, enhancing electoral oversight mechanisms, and implementing continuous women’s political empowerment programs at the local level to transform women’s representation from symbolic participation into substantive political influence.